توجيه القراءات من خلال شروح الشاطبية - إبراز المعاني من حرز الأماني لأبي شامة المقدسي رحمه الله ( ت 665 ه) نموذجا - - شرقي, فاطمة; قعيد, خديجة (University of eloued جامعة الوادي, 2021)
الحمد لله رب العالمين والصلاة والسلام على خاتم الأنبياء والمرسلين المبعوث رحمة للعالمين وعلى اله وصحبه اجمعين وبعد يعالج هذا الموضوع المعنون ب توجيه القراءات القرآنية من خلال شروح الشاطبية إبراز المعاني انموذجا وقد كانت الخطة الاجمالية لهذا البحث مكونة من مقدمة ومبحثين وخاتمة فلقد وقفنا خلال هذه الدراسة على تعريف علم القراءات وذكر بعض قواعده وأنواعه وأدواته كما أننا عرفنا بالإمام الشاطبي ومنظومته والامام ابي شامة وكتابه إبراز المعاني ثم تتبعنا هذا الأخير وذلك باستخراج أمثلة تطبيقية مع توظيف أدوات التوجيه وإبراز شيء من منهج الإمام ابي شامة في التوجيه ثم ختمنا بحثنا بخاتمة بينا فيها أهم النتائج المتوصل إليها.Praise be to God, Lord of the Worlds, and prayers and peace be upon the Seal of the Prophets and Messengers, who was sent as a mercy to the worlds, and upon his family and companions altogether. This topic, entitled “Guiding Qur’anic readings” through the explanations of Al-Shatibya, deals with highlighting the meanings as an example The overall plan of this research consisted of an introduction, two chapters, and a conclusion During this study, we came to define the science of readings and mentioned some of its rules, types and tools. We also got to know Imam Al-Shatibi and his system, and Imam Abi Shama and his book Highlighting Meanings. Then we followed the latter by extracting applied examples with the use of guidance tools and highlighting something from Imam Abi Shama’s approach to guidance. Then we concluded our research with a conclusion in which we showed the most important results
لغة ودراسات
Keywords: توجيه القراءات - أبي شامه - شروح الشاطبية - إبراز المعاني من حرز الأماني; Guiding the Readings - Abi Shama - Explanations of Shatbya - Highlighting the meanings from the wish list